Chorioretinopathy Post COVID-19: A Systematic Review and Prevalence Assessment, Unveiling Insights into an Emerging Ocular Entity - Mona Mahmoud Elsakka (19487698) (2024)
Purpose To investigate the occurrence of chorioretinopathy post-COVID-19, emphasizing demographic characteristics, medication history, clinical presentation, diagnostic evaluation, and treatment approaches, with a specific focus on the role of corticosteroid use. Methods Our protocol was registered prospectively on PROSPERO (CRD42023457712). A systematic search of databases (PubMed, Cochrane, WOS, Scopus) from November 2020 to August 2023 were performed to identify any original research reporting chorioretinopathy in COVID-19 patients. Data extraction included patient demographics, COVID-19 timeline, medication history, symptoms, diagnostic tests, and treatment outcomes. We used Joanna Briggs Institute (JBI) critical appraisal tool to assess the quality of our included studies. Results We identified seven case reports and two case series including 10 patients, six females and four males (mean age 36.5 years), who exhibited chorioretinopathy after COVID-19. Onset varied from 6 days to three months post-infection (average = 24.3 days). Seven patients (70%) had a history of corticosteroid use during COVID-19 treatment. Symptoms included visual loss, blurred vision, and deterioration. Diagnostic assessments revealed central serous chorioretinopathy in seven patients (70%) and punctate inner choroidopathy in two (20%). Treatment approaches varied, with corticosteroid discontinuation leading to symptom improvement, while two patients were treated with corticosteroids. Five patients who discontinued corticosteroids were reported to have improvement in visual acuity, two of them changed to 20/25 after being 20/40, two changed to 6/6, and one changed to 20/20, while the visual acuity in the sixth patient was not reported. Regarding the two patients who were treated with corticosteroids, visual acuity was reported in one case only and it improved to 20/20. Conclusion This systematic review states the prevalence and potential association between chorioretinopathy, and corticosteroid use in the context of COVID-19. This relation is still unclear because of the relief of symptoms in some cases after corticosteroid discontinuation, while two other cases were treated with corticosteroids and their symptoms improved. Other Information Published in: Seminars in Ophthalmology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/08820538.2024.2323113